Investigation of optical prechamber spark plug and dual laser pulses for ignition - Loccisano, Frank Christopher, author; Yalin, Azer P., 1972-, advisor; Marchese, Anthony John, 1967-, committee member; Roberts, Jacob L., committee member (Colorado State University. Libraries, 2011)
Laser ignition has the potential to increase efficiency and reduce pollutant emissions of natural gas engines. The work presented in this thesis focuses on investigate the reasons behind lower indicated mean effective pressures (IMEPs) obtained in laser ignition tests of Caterpillar G3516C engine when operated with hollow core fibers, and experimentally investigating the effect of using dual laser pulses to increase the total amount of energy deposited in a laser spark. To address the low IMEP, succinct tests were performed on the Caterpillar G3516C engine with a non-fueled electric prechamber plug, a non-fueled laser prechamber plug, and an open chamber laser plug. Test data showed that the open chamber laser plug exhibited a high degree of combustion instability, while the prechamber electrical and laser plug showed similar (improved) performance with the prechamber laser plug having a slightly higher degree of combustion variability. Computational fluid dynamics (CFD) was performed to examine the turbulent flow inside the optical prechamber. The CFD found that to optimize the use of the optical prechamber the spark should be located in the bottom half of the prechamber to reduce the quenching due to turbulence. Bench top experiments were also performed to examine the possibility of increasing the energy in the laser spark by employing dual laser pulses. The first pulse would initiate the spark while the second pulse deposits additional energy into the spark. It was shown that initial spark can absorb 80 to 90% energy of the second pulse if the inter-pulse separation (Δt) is about 20 to 40 nanoseconds. Overall, better understanding of the use of optical prechamber sparkplugs, as well as the use of dual laser pulses to increase the amount of energy deposited into the spark, will aid in the progression of a practical laser ignition system.
Keywords: CFD; dual pulse; ignition; laser; plasma; prechamber